Pelatihan Jurnalisme Investigasi Bagi Mahasiswa Jurnalistik UTU dan UIN Ar-Raniry di Banda Aceh dan Aceh Besar - Muzakkir Muzakkir; Murhaban Murhaban; Teuku Farizal; Ismu Ridha; Iwan Doa Sempena; Futri Syam; Suryadi Suryadi; Mukhlizar Mukhlizar (Universitas Teuku Umar, 2024)
In today's digital era, the continuous advancement of information has become meaningful in societal life. The development of investigative journalism exposes various irregularities or hidden issues covered up by state officials or authorities entrusted with the responsibility to manage and control various resources for the public's benefit. Additionally, investigative journalism is a methodological discipline, requiring opportunities to be understood and mastered. Thus, aspiring journalists need intelligence and agility to examine, research, and deconstruct journalistic knowledge to reveal hidden cases, prepared to face resistance, challenges, and threats. The purpose of this investigative journalism training for prospective journalists is to enable students to fully understand investigative reporting, which demands mental resilience and courage to disclose cases deliberately concealed. The benefit of this activity is to inspire students, as future journalists, to engage critically and insightfully with information evolving across various channels. As aspiring journalists, critical thinking is essential in addressing rumors, emerging public issues, and a skeptical stance toward information disseminated by certain parties, emphasizing the need for thorough verification. The direction and objective of this training for prospective journalists are to foster understanding and the ability to think critically in investigating and researching events or cases suspected of irregularities. This training employs lecture and discussion methods. The outcomes for aspiring journalists are to inspire, motivate, and express their investigative journalism work, serving as a medium to report events or cases suspected of anomalies to the public. Consequently, media users can better understand news or rumors constructed by aspiring journalists, which is then widely disseminated to the public.